Multimedia Engineering Drawing Animations to Improve Vocational High School Students' Technical Drawing Concepts - Mujiarto Mujiarto; M Komaro; A Djohar (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of the research to develop innovative multimedia animation engineering drawing (MMAED) in the field of technology and engineering in Vocational High Schools. The research method used is research and development which broadly covers the manufacturing, and testing stages. The study population was vocational students in the fields of technology and engineering expertise. Learning is done in two different classes, namely: Class A as a control class, and class B as an experimental class. Data collection tools in the form of tests, rubrics, and questionnaires. Data were analyzed by descriptive analysis, percentage, and N-gain. The results of this study are Multimedia Animation Engineering Drawing (MMAED) with special characteristics that are accessible or affordable to the eyes and logic of students, by orthogonal projection material that requires imagination or imagination of the appearance of an object. The mastery of the concept of orthogonal projection material has increased after using MMAED, so that it reaches a high category.